Assessment of HEFA, ATJ, GTL-S8 and Farnesane as alternative jet fuels based on their water shedding characteristics - Ugbeh, Judith (Cranfield University, 2022)
Previous studies have shown that impurities like surfactants in jet fuel have impacted the performance of coalescer filters. Therefore, aircraft maintenance schedules require an additional operation which is commonly known as water sumping. Normally after bulk fuel transfers, fuels are allowed to settle in tanks and sumping is carried out to remove free water. Water settling tests can indirectly measure surfactants in jet fuels, yet there is no reliable data that focuses on the water settling rate of alternative jet fuels that comply with or are very similar to the Jet A-1 specification. Additionally, the influence of the jet fuel composition on the rate of water-shedding is still unknown. Therefore, there is a need for a reliable study to fill this lack of knowledge. In this work, the water settling rate of five different jet fuels made to different national standards in comparison to conventional Jet A-1 fuel was evaluated. GTL S-8, HEFA and ATJ has been identified as potential/alternative candidates for ASTM D7566 certified jet fuels.
Keywords: 'aviation fuel'; 'Water solubility'; 'Sustainable fuel'; 'alternative fuels'; 'Settling velocity'; 'Aerospace Engineering'